Regulatory and legal support of organization of organic land use and ways of its improvement - Dorosh, Y.; Barvinskyi, A.; Dorosh, O.; Melnyk, D.; Vysidalko, A. (Land Management, Cadastre and Land Monitoring, 2021)
The article analyses the regulatory and legal support for the organization of organic land use in Ukraine. It is established that the current regulations in the field of organic production are aimed mainly at regulating the technological processes of organic production, the procedure for its certification and the market of organic products. At the same time, the legislators did not pay attention to the issues related to the organization of the territory of agricultural enterprises for the production of organic products in order to meet the requirements of the relevant standards and rules of IFOAM.It is proved that for the organization of the territory of organic land use and land tenure it is necessary to develop and implement appropriate land management projects. In view of this, it is necessary to amend the Law of Ukraine "On Land Management", supplementing Article 25 with a new type of land management documentation: land management projects for the organization of organic land use (land tenure), and to enshrine the composition and content of such land management projects.Key words: normative-legal regulation, organic land use, buffer zone, crop rotation, land management project.